2016
DOI: 10.1038/srep34354
|View full text |Cite
|
Sign up to set email alerts
|

BEN domain protein Elba2 can functionally substitute for linker histone H1 in Drosophila in vivo

Abstract: Metazoan linker histones are essential for development and play crucial roles in organization of chromatin, modification of epigenetic states and regulation of genetic activity. Vertebrates express multiple linker histone H1 isoforms, which may function redundantly. In contrast, H1 isoforms are not present in Dipterans, including D. melanogaster, except for an embryo-specific, distantly related dBigH1. Here we show that Drosophila BEN domain protein Elba2, which is expressed in early embryos and was hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Nearly complete resonance assignments were obtained for this construct using standard double and triple resonance experiments. NMR structures were generated using a combination of CYANA distance geometry calculations [ 51 , 52 , 53 ] and restrained molecular dynamics refinements in AMBER [ 54 ]. The 20 conformers with the lowest restraint violation energy were selected for the final representative ensemble and are shown in Figure 3 A and Figure S4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly complete resonance assignments were obtained for this construct using standard double and triple resonance experiments. NMR structures were generated using a combination of CYANA distance geometry calculations [ 51 , 52 , 53 ] and restrained molecular dynamics refinements in AMBER [ 54 ]. The 20 conformers with the lowest restraint violation energy were selected for the final representative ensemble and are shown in Figure 3 A and Figure S4 .…”
Section: Resultsmentioning
confidence: 99%
“…Analyses revealed the association between the BEN domains and specific DNA binding through extensive nucleotide contacts with their α helices and C-terminal loop, suggesting that the BEN domain functions in a DNA sequence-specific manner. On the other hand, recently, the Drosophila BEN-solo protein Elba2, but not Insv, was shown to rescue the deficiency of histone H1 protein in early larvae [ 53 ], supporting the sequence-recognition specificity and sequence-specific function of BEN domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BEN domains are proposed to function as adaptors to promote the assembly of higher-order chromatin, or to regulate chromatin remodeling during transcription ( 44 47 ). Indeed, the Drosophila melanogaster Elba2 protein has been shown to functionally substitute for histone H1 if the natural linker histone is depleted from cells ( 48 ). The structures of the insv-BEN and the Bsg25A BEN domains from Drosophila ( 33 , 34 ) have revealed that the association of BEN domains with DNA is generally accomplished through the insertion of both the loop located between the α2 and α3 helices and the long C-terminal helix into two consecutive major grooves of the nucleic acid molecule (Figure 5A ; Supplementary Figure S6A and B ).…”
Section: Discussionmentioning
confidence: 99%